Influence of cadmium sulfate at different doses on the functional state of the liver of laying chicken - A. Y. Ostapyuk; B. V. Gutyj (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
The article presents the results of studies on the influence of cadmium sulfate in different doses on the organism of poultry. Absorbed cadmium accumulates in the liver as a complex with metallothionein. The purpose of the work was to find out the effect of cadmium sulfate in doses of 2 and 4 mg / kg of body weight on the functional state of the liver of chicken. For research, three groups of birds were formed: control and two experimental. The control group of chickens were in the usual diet, they were fed with forage and were given water without introducing cadmium sulfate. To the drinking water of chickens of experimental groups for 30 days, added cadmium sulfate in doses: the first group – 2 mg/kg, the second group – 4 mg/kg body weight. The conditions for keeping chickens and the microclimate parameters in the room for all bird groups were similar. Blood from the chickens was taken from the subclavian vein in periods: before the dasg was given and on the first, seventh, fourteenth, twenty-first and thirtieth day of the experiment. It was determined that the presentation of cadmium sulfate in doses of 2 and 4 mg/kg of body weight of cows, which contributed to a violation of the functional state of the liver, as evidenced by the increased activity of aminotransferases in their blood serum. The activity of alanine and aspartate aminotransferase was higher in serum of blood of chickens in the second experimental group at 21st and 30th days of the experiment. The high activity of aminotransferases in the blood serum of chickens for cadmium loading indicates destructive processes in the liver that cause an increase in the release of aminotransaminases from cellular organelles in the blood of experimental poultry. Thus, the obtained results indicate an increase in destructive processes in the body of chickens for cadmium loading.